Nanoscale analysis of caspofungin-induced cell surface remodelling in Candida albicans - El-Kirat-Chatel, Sofiane (2012)
The advent of fungal pathogens that are resistant to the classic repertoire of antifungal drugs has increased the need for new therapeutic agents. A prominent example of such novel compound is caspofungin, known to alter cell wall biogenesis by inhibiting β-1,3 D-glucan synthesis. Although much progress has been made in understanding the mechanism of action of caspofungin, little is known about its influence on the biophysical properties of the fungal cells. Here, we use atomic force microscopy to demonstrate that caspofungin induces major remodeling of the cell surface properties of Candida albicans. Caspofungin causes major morphological and structural alterations of the cells, which correlate with a decrease of the cell wall mechanical strength. Moreover, we find that the drug induces the massive exposure of the cell adhesion protein Als1 on the cell surface and leads to increased cell surface hydrophobicity, two features that trigger cell aggregation. This behaviour is not observed in yeast species lacking Als1, demonstrating the key role that the protein plays in determining the aggregation phenotype of C. albicans. The results show that AFM opens up new avenues for understanding the molecular bases of microbe-drug interactions and for developing new therapeutic agents.